2015
DOI: 10.3138/ptc.2013-72
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Professional Behaviour in Canadian Physical Therapy Students' Objective Structured Clinical Examinations: An Environmental Scan

Abstract: Purpose: To identify professional behaviours measured in objective structured clinical examinations (OSCEs) by Canadian university physical therapy (PT) programs. Method: A cross-sectional telephone survey was conducted to review current practice and determine which OSCE items Canadian PT programs are using to measure PT students' professional behaviours. Telephone interviews using semi-structured questions were conducted with individual instructors responsible for courses that included an OSCE as part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…4,5 In a previous national study, 11 participants identified 31 PBs as items that have been assessed in an OSCE context. Feasibility is an important consideration in the assessment of PBs, 23 and we eliminated several items during our consensus exercise because they were deemed infeasible in an OSCE context.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4,5 In a previous national study, 11 participants identified 31 PBs as items that have been assessed in an OSCE context. Feasibility is an important consideration in the assessment of PBs, 23 and we eliminated several items during our consensus exercise because they were deemed infeasible in an OSCE context.…”
Section: Discussionmentioning
confidence: 99%
“…11 It gives students an opportunity to be evaluated on their clinical skills and PBs. The feedback that students receive in PB assessment can be valuable to those still struggling to integrate these complex behaviours into their clinical practice (e.g., effective communication, respect).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, professionalism is difficult to defined [5], taught and assessed [4,6,7]. The importance of teaching and measuring professionalism is undoubtedly in professional education of healthcare [4,6,8,9,10].…”
Section: Introductionmentioning
confidence: 99%